Sulfur positive electrode material of energy storage battery as well as preparation method and application of sulfur positive electrode material
By spreading the single sulfur evenly to the carbon material substrate, the problem of insufficient performance of the existing energy storage battery orthopedic materials was solved, and the positive electrode material of the energy storage battery of high -conductivity and long cyclic life was realized.
Patent Information
- Application Number
- CN202411330755.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-24
Smart Images

Figure CN119361625A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sulfur positive electrode material for an energy storage battery and a preparation method and application thereof, belonging to the technical field of batteries. Background Art
[0002] With the rapid development of power generation technology, wind power generation technology and photovoltaic power generation technology have become the mainstream power generation system. Photovoltaic power station refers to a photovoltaic power generation system that is connected to the power grid and transmits electricity to the power grid. Photovoltaic power stations mainly use solar energy to generate electricity. During the power generation process, the excess electricity will be stored in energy storage batteries. Lithium batteries have the characteristics of small size, light weight, and strong power storage capacity, and are widely used in the field of energy storage. However, with the development of photovoltaic technology, the requirements for energy storage batteries are getting higher and higher. Ordinary lithium-ion batteries can no longer meet the energy storage needs of high-performance photovoltaic batteries, including energy density and cycle life. As one of the key materials for energy storage batteries, the performance of the positive electrode material directly determines the performance of the battery. Therefore, the preparation of a high-performance positive electrode material is the key to achieving high-capacity and long-cycle energy storage batteries. Summary of the invention
[0003] In view of this, the present invention provides a sulfur positive electrode material for an energy storage battery, a preparation method and an application thereof. The technical problem to be solved is to use a carbon material as a matrix material to uniformly diffuse the elemental S into the carbon material matrix, thereby achieving uniform contact between the elemental S and the carbon matrix, and providing sufficient electrons for the redox reaction of the elemental S during the charge and discharge process, so as to improve the conductivity of the positive electrode material.
[0004] To achieve the above-mentioned object, the present invention provides a sulfur positive electrode material for an energy storage battery, wherein the sulfur positive electrode material for the energy storage battery comprises elemental sulfur and a carbon material matrix, wherein the carbon material matrix is loaded with elemental sulfur; the carbon material matrix comprises graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth and a mixture of any two thereof.
[0005] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0006] Preferably, in the aforementioned sulfur positive electrode material for energy storage batteries, the mass ratio of the carbon material matrix to elemental sulfur is 1:9 to 4:6; the carbon material matrix is selected from a mixture of any two of graphite, graphene, carbon nanotubes, amorphous carbon and carbon cloth, and the mass ratio of the mixture of any two of them is 1:2 to 2:1.
[0007] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. A method for preparing a sulfur positive electrode material for an energy storage battery proposed in the present invention comprises the following steps:
[0008] The elemental sulfur and the carbon material matrix are mixed evenly and calcined so that the elemental sulfur is loaded on the carbon material matrix.
[0009] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0010] Preferably, the aforementioned method for preparing the sulfur positive electrode material for the energy storage battery comprises the following steps:
[0011] 1) adding a carbon material matrix to elemental sulfur and grinding them until the elemental sulfur and the carbon material matrix are evenly mixed to obtain a mixed powder;
[0012] 2) The mixed powder obtained in step 1) is calcined at high temperature under inert gas conditions to obtain the sulfur positive electrode material for the energy storage battery.
[0013] Preferably, in the aforementioned method for preparing sulfur positive electrode materials for energy storage batteries, in step 1), the mass ratio of the carbon material matrix to elemental sulfur is 1:9 to 4:6.
[0014] Preferably, in the aforementioned method for preparing sulfur positive electrode materials for energy storage batteries, in step 1), the carbon material matrix includes graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth and a mixture of any two thereof.
[0015] Preferably, in the aforementioned method for preparing sulfur positive electrode materials for energy storage batteries, in step 1), the grinding time is 1 h to 12 h.
[0016] Preferably, in the aforementioned method for preparing sulfur positive electrode material for energy storage battery, in step 2), the temperature of high temperature calcination is 120-200°C.
[0017] Preferably, in the aforementioned method for preparing sulfur positive electrode materials for energy storage batteries, in step 2), the high-temperature calcination time is 6 h to 24 h.
[0018] Preferably, in the aforementioned method for preparing sulfur positive electrode materials for energy storage batteries, in step 2), the inert gas is high-purity argon gas with a purity of 99.99%.
[0019] The purpose of the present invention and the solution to its technical problems can also be achieved by adopting the following technical measures: The present invention provides an energy storage battery, comprising a positive electrode, wherein the positive electrode adopts the above-mentioned energy storage battery sulfur positive electrode material.
[0020] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0021] Compared with the prior art, the energy storage battery sulfur positive electrode material and its preparation method and application described in the present invention have the following beneficial effects:
[0022] The present invention uses carbon material as a matrix material, uniformly diffuses elemental S onto the carbon material matrix, achieves uniform contact between elemental S and the carbon matrix, and provides sufficient electrons for the redox reaction of elemental S during the charge and discharge process, thereby improving the conductivity of the positive electrode material; at the same time, the carbon matrix can buffer the volume strain generated by elemental S during the lithium insertion / delithiation process, thereby improving the cycle life of the battery; the carbon matrix can physically block the dissolution of polysulfide into the electrolyte, thereby effectively improving the problem of low specific capacity caused by the shuttle effect;
[0023] The energy storage battery of the present invention has a capacity retention rate of 70-82% after 1000 cycles at 1C, a first-cycle discharge specific capacity of 985-1149 mAh / g at 0.1C, a first-cycle discharge specific capacity of 952-1091 mAh / g at 0.2C, a first-cycle discharge specific capacity of 886-993 mAh / g at 0.5C, and a first-cycle discharge specific capacity of 763-885 mAh / g at 1C.
[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic structural diagram of the sulfur positive electrode material of the energy storage battery of the present invention;
[0026] Figure 2 The present invention is a flow chart of the method for preparing the sulfur positive electrode material for energy storage batteries. DETAILED DESCRIPTION
[0027] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a sulfur positive electrode material for energy storage batteries and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0028] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0029] like Figure 1As shown, some embodiments of the present invention provide a sulfur positive electrode material for an energy storage battery, the sulfur positive electrode material for an energy storage battery comprises elemental sulfur 1 and a carbon material matrix 2, the elemental sulfur 1 is loaded on the carbon material matrix 2; wherein the carbon material matrix 2 comprises graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth and a mixture of any two thereof. The carbon material matrix has oxygen-containing functional groups such as carboxyl and hydroxyl groups, which will generate intermolecular forces with sulfur atoms.
[0030] In a specific implementation, the mass ratio of the carbon material matrix to elemental sulfur is 1:9 to 4:6; the mass ratio of the mixture of any two is 1:2 to 2:1. In addition, the carbon material matrix 2 is preferably a mixture of graphene and carbon nanotubes.
[0031] Furthermore, the loading rate of the elemental sulfur 1 is 60-90%, which is related to the mass ratio of the carbon material matrix 2 and the elemental sulfur 1.
[0032] See also Figure 2 Some embodiments of the present invention also provide a method for preparing the above-mentioned sulfur positive electrode material for energy storage batteries, comprising the following steps:
[0033] The elemental sulfur and the carbon material matrix are mixed evenly and calcined to load the elemental sulfur on the carbon material.
[0034] In specific implementation, the preparation method comprises the following steps:
[0035] S1: Weigh a certain amount of elemental sulfur and place it in a grinder, add a carbon material matrix, and obtain a mixed powder;
[0036] S2: Grind the mixed powder obtained in S1 with a grinder for a period of time until the elemental sulfur and the carbon material matrix are evenly mixed;
[0037] S3: The uniformly mixed powder is placed in a tubular furnace and calcined at high temperature for a period of time under inert gas conditions to obtain an S / carbon matrix positive electrode material.
[0038] In the specific implementation, elemental S is used as the positive electrode to provide capacity, and the carbon material is used as an additive to provide conductivity, so there is an optimal ratio between the two; optionally, the mass ratio of the carbon material matrix and elemental sulfur in step S1 can be 1:9 to 4:6, for example 1:9, 2:8, 3:7, 4:6. If the mass ratio of the two is less than 1:9, the carbon material matrix is too small and the conductivity provided is insufficient, affecting the performance; if the mass ratio of the two is greater than 4:6, the carbon material matrix is excessive, which increases the weight and volume of the positive electrode side and reduces the specific capacity and volume capacity; preferably it is 2:8, so that the S positive electrode requires the participation of electrons during the charging and discharging process, and the preferred ratio can provide sufficient conductivity without reducing the capacity.
[0039] In some embodiments, optionally, the carbon material matrix described in step S1 is graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth, and a mixture of any two thereof. The single substance S is used as the positive electrode material, and its intrinsic insulation leads to poor electrical properties, and a conductive material needs to be added. Among them, graphite, graphene, and carbon nanotubes have excellent electrical conductivity, and graphene and carbon nanotubes have better electrical conductivity, so a mixture of graphene and carbon nanotubes is preferred;
[0040] Taking into account the influence of the type of carbon material matrix and the mass ratio of the carbon material matrix to elemental S on the electrochemical properties of elemental S, in some embodiments, optionally, the mass ratio of the mixture of any two kinds in step S1 can be set to 1:2 to 2:1, for example, 1:1, 1:2, 2:1. When the matrix is a mixture of graphene and carbon nanotubes, it is preferably 1:1.
[0041] In some embodiments, optionally, the grinding time described in step S2 can be set to 1h~12h, which is set to fully mix the elemental S powder and the carbon material powder; if the grinding time is less than 1h, the time is too short and the mixing is uneven; if the grinding time is greater than 12h, the time is too long and the shape of the carbon material itself will be destroyed; preferably 6h, so that the elemental S and the carbon material can be evenly mixed without affecting the shape of the carbon material itself.
[0042] In some embodiments, optionally, in step S3, the temperature of the high temperature calcination is 120-200°C. The purpose of this setting is to keep the elemental S in a molten state so that it can easily diffuse into the carbon material matrix. If the temperature of the high temperature calcination is lower than 120°C, the temperature does not reach the melting point of S; if the temperature of the high temperature calcination is higher than 200°C, it will cause a waste of electricity and time; in order to ensure that S can be optimally melted, the temperature of the high temperature calcination is preferably 155°C. The time of the high temperature calcination is 2h to 12h; if it is less than 2h, the melting and diffusion time of S is short, which may easily lead to uneven diffusion of S on the carbon material matrix; if it is greater than 12h, it will cause a waste of electricity and time; considering the uniformity of the diffusion of S on the carbon material matrix, the time of the high temperature calcination is preferably 6h. The inert gas can be high-purity argon with a purity of 99.99%.
[0043] In the above technical scheme, the present invention uniformly disperses the carbon material matrix and the elemental S by uniformly diffusely regulating the elemental S on the carbon material matrix, thereby improving the conductivity of the positive electrode material and buffering the strain generated by the elemental S during the lithium insertion / delithiation process, thereby improving the cycle life of the battery; the carbon material matrix inhibits the shuttle effect of polysulfide through physical barrier effect, thereby improving the utilization rate of the active sulfur positive electrode; the uniform diffusion of the elemental S on the carbon material matrix is achieved by the method of inert gas regulation; the designed positive electrode material can buffer the strain generated by the elemental S during the lithium insertion / delithiation process, and at the same time has the function of physical barrier, thereby achieving the purpose of improving battery performance.
[0044] Some embodiments of the present invention further provide an energy storage battery, comprising a positive electrode, wherein the positive electrode adopts the above-mentioned energy storage battery sulfur positive electrode material. Specifically, the energy storage battery is an energy storage lithium sulfur battery.
[0045] The present invention is further described below in conjunction with specific embodiments.
[0046] Example 1
[0047] See also Figure 1 This embodiment provides a sulfur positive electrode material for an energy storage battery, the sulfur positive electrode material for an energy storage battery comprising elemental sulfur 1 and a carbon material matrix 2, the carbon material matrix 2 being loaded with elemental sulfur 1. The carbon material matrix 2 is a mixture of graphene and carbon nanotubes, the mass ratio of the two being 1:1; the mass ratio of the carbon material matrix 2 to the elemental sulfur 1 is 2:8. The loading rate of the elemental sulfur 1 is 80%.
[0048] The method for preparing the above-mentioned sulfur positive electrode material for energy storage battery comprises the following steps:
[0049] S1: According to the above mass ratio, elemental sulfur 1 is weighed and placed in a grinding jar, and a carbon material matrix 2 is added;
[0050] S2: grinding the first mixed powder obtained in step S1 with a grinder for 6 hours until the elemental sulfur 1 and the carbon material matrix 2 are evenly mixed;
[0051] S3: placing the second powder mixed evenly in step S2 in a tubular furnace, and calcining it at 155° C. for 6 hours under the condition of high-purity argon gas with a purity of 99.99%, to obtain an S / carbon matrix positive electrode material, i.e., the sulfur positive electrode material for the energy storage battery.
[0052] Example 2
[0053] The difference between this embodiment and embodiment 1 is that the mass ratio of the carbon material matrix 2 and the elemental sulfur 1 in this embodiment is 1:9; the loading rate of the elemental sulfur 1 is 90%, and the other parameters and steps are the same as those in embodiment 1.
[0054] Example 3
[0055] The difference between this embodiment and embodiment 1 is that the mass ratio of the carbon material matrix 2 and the elemental sulfur 1 in this embodiment is 3:7; the loading rate of the elemental sulfur 1 is 70%, and the other parameters and steps are the same as those in embodiment 1.
[0056] Example 4
[0057] The difference between this embodiment and embodiment 1 is that the mass ratio of the carbon material matrix 2 and the elemental sulfur 1 in this embodiment is 4:6; the loading rate of the elemental sulfur 1 is 60%, and the other parameters and steps are the same as those in embodiment 1.
[0058] Example 5
[0059] The difference between this embodiment and embodiment 1 is that the grinding time in step S2 of this embodiment is 1 hour, and the other parameters and steps are the same as those in embodiment 1.
[0060] Example 6
[0061] The difference between this embodiment and embodiment 1 is that the grinding time in step S2 of this embodiment is 3 hours, and the other parameters and steps are the same as those in embodiment 1.
[0062] Example 7
[0063] The difference between this embodiment and embodiment 1 is that the grinding time in step S2 of this embodiment is 5 hours, and the other parameters and steps are the same as those in embodiment 1.
[0064] Example 8
[0065] The difference between this embodiment and embodiment 1 is that the grinding time in step S2 of this embodiment is 8 hours, and the other parameters and steps are the same as those in embodiment 1.
[0066] Example 9
[0067] The difference between this embodiment and embodiment 1 is that the grinding time in step S2 of this embodiment is 10 hours, and the other parameters and steps are the same as those in embodiment 1.
[0068] Example 10
[0069] The difference between this embodiment and embodiment 1 is that the grinding time in step S2 of this embodiment is 12 hours, and the other parameters and steps are the same as those in embodiment 1.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that this comparative example does not contain the carbon material matrix 2, and the elemental sulfur 1 is directly used as the sulfur positive electrode material of the energy storage battery.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that the mass ratio of the carbon material matrix 2 and the elemental sulfur 1 in this comparative example is 1:10, and the other parameters and steps are the same as those in Example 1.
[0074] Comparative Example 3
[0075] The difference between this comparative example and Example 1 is that the mass ratio of the carbon material matrix 2 and the elemental sulfur 1 in this comparative example is 5:6, and the other parameters and steps are the same as those in Example 1.
[0076] Comparative Example 4
[0077] The difference between this comparative example and Example 1 is that the grinding time described in step S2 of this comparative example is 0.5 h, and the other parameters and steps are the same as those in Example 1.
[0078] Comparative Example 5
[0079] The difference between this comparative example and Example 1 is that the grinding time described in step S2 of this comparative example is 13 hours, and the other parameters and steps are the same as those in Example 1.
[0080] The sulfur positive electrode materials, separators, electrolytes and lithium negative electrodes prepared in the above Examples 1-10 and Comparative Examples 1-5 were assembled into energy storage batteries, and their electrochemical properties, including rate performance and cycle performance, were tested. The test results are shown in Table 1. The charge and discharge voltage for testing the electrochemical performance was set to 1.5 V-3.0 V. In the rate performance test, the current density was set to 0.1 C, 0.2 C, 0.5 C, 1 C, 0.5 C, and 0.2 C, respectively.
[0081] Table 1
[0082]
[0083] It can be seen from the data in Table 1 that the energy storage batteries of Examples 1-10 of the present invention have a capacity retention rate of 70-82% after 1000 cycles at 1C, a first-cycle discharge capacity of 985-1149mAh / g at 0.1C, a first-cycle discharge capacity of 952-1091mAh / g at 0.2C, a first-cycle discharge capacity of 886-993mAh / g at 0.5C, and a first-cycle discharge capacity of 763-885mAh / g at 1C. Among them, the first-cycle discharge capacity at a current density of 0.1C can reach up to 1149mAh / g. In the cycle performance test, after 1000 cycles at a current density of 1C, the specific capacity was maintained at a maximum of 885mAh / g, and the capacity retention rate was 82%.
[0084] Compared with Example 1, as the mass ratio of the carbon material matrix and elemental sulfur decreases, the capacity retention rate of Example 2 after 1000 cycles at 1C decreases; as the mass ratio of the carbon material matrix and elemental sulfur increases, the capacity retention rates of Examples 3 and 4 after 1000 cycles at 1C decrease; this is because the carbon material matrix improves the conductivity of the positive electrode material, buffers the strain generated by the elemental S during the lithium insertion / delithiation process, and can improve the cycle performance of the battery.
[0085] Compared with Example 1, as the grinding time described in step S2 is reduced, the capacity retention rate of Examples 5, 6, and 7 after 1000 cycles at 1C is reduced; as the grinding time described in step S2 is increased, the capacity retention rate of Examples 8, 9, and 10 after 1000 cycles at 1C is reduced; this is because the mixing uniformity of elemental S and carbon material affects the electrochemical properties of the lithium-sulfur battery, and the more uniform the mixing, the better the electrochemical properties; if the grinding time is too long, the original structure of the carbon material is destroyed and the conductive performance is affected.
[0086] Compared with Example 1, Comparative Example 1 does not contain a carbon material matrix, and elemental sulfur is directly used as the sulfur positive electrode material of the energy storage battery. Its capacity retention rate after 1000 cycles at 1C is greatly reduced; this is because elemental sulfur has intrinsic insulation. When used as a positive electrode, the redox reaction during the charge and discharge process requires electron transfer, and conductive materials are required to supplement electrons. When there are only a small amount of electrons, the redox reaction is insufficient and the capacity retention rate will be greatly reduced.
[0087] Compared with Example 1, as the mass ratio of the carbon material matrix and elemental sulfur decreases and the mass ratio of the two is not within the protection scope of the present invention, the capacity retention rate of Comparative Example 2 after 1000 cycles at 1C is greatly reduced; as the mass ratio of the carbon material matrix and elemental sulfur increases and the mass ratio of the two is not within the protection scope of the present invention, the capacity retention rate of Comparative Example 3 after 1000 cycles at 1C is greatly reduced;
[0088] Compared with Example 1, as the grinding time described in step S2 is reduced and it is not within the scope of protection of the present invention, the capacity retention rate of comparative example 4 after 1000 cycles at 1C is greatly reduced; as the grinding time described in step S2 is increased and it is not within the scope of protection of the present invention, the capacity retention rate of comparative example 5 after 1000 cycles at 1C is greatly reduced.
[0089] The above embodiments are only used to explain the content of the present invention, and are not intended to limit the present invention. Simple technical variations within the technical concept of the present invention should be considered to be covered by the content disclosed by the present invention and belong to the protection scope of the present invention.
[0090] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0091] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0092] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A sulfur positive electrode material for an energy storage battery, characterized in that: The energy storage battery sulfur positive electrode material comprises elemental sulfur and a carbon material matrix, wherein the carbon material matrix is loaded with elemental sulfur; the carbon material matrix comprises graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth and a mixture of any two thereof.
2. The sulfur positive electrode material for energy storage battery according to claim 1, characterized in that: The mass ratio of the carbon material matrix to elemental sulfur is 1:9 to 4:6; the carbon material matrix is selected from a mixture of any two of graphite, graphene, carbon nanotubes, amorphous carbon and carbon cloth, and the mass ratio of the mixture of any two of them is 1:2 to 2:
1.
3. A method for preparing a sulfur positive electrode material for an energy storage battery, characterized in that: The following steps are involved: The elemental sulfur and the carbon material matrix are mixed evenly and calcined so that the elemental sulfur is loaded on the carbon material matrix.
4. The method for preparing the sulfur positive electrode material for energy storage battery according to claim 3, characterized in that: The preparation method comprises the following steps: 1) adding a carbon material matrix to elemental sulfur and grinding them until the elemental sulfur and the carbon material matrix are evenly mixed to obtain a mixed powder; 2) The mixed powder obtained in step 1) is calcined at high temperature under inert gas conditions to obtain the sulfur positive electrode material for the energy storage battery.
5. The method for preparing the sulfur positive electrode material for energy storage battery according to claim 4, characterized in that: In step 1), the mass ratio of the carbon material matrix to elemental sulfur is 1:9 to 4:
6.
6. The method for preparing the sulfur positive electrode material for energy storage battery according to claim 4, characterized in that: In step 1), the carbon material matrix includes graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth and a mixture of any two thereof; the mass ratio of the mixture of any two thereof is 1:2 to 2:
1.
7. The method for preparing the sulfur positive electrode material for energy storage battery according to claim 4, characterized in that: In step 1), the grinding time is 1 h to 12 h.
8. The method for preparing the sulfur positive electrode material for energy storage battery according to claim 4, characterized in that: In step 2), the high temperature calcination temperature is 120-200°C.
9. The method for preparing the sulfur positive electrode material for energy storage battery according to claim 4, characterized in that: In step 2), the high temperature calcination time is 6 hours to 24 hours; the inert gas is high-purity argon gas with a purity of 99.99%.
10. An energy storage battery, comprising a positive electrode, characterized in that the positive electrode adopts a sulfur positive electrode material for an energy storage battery; the sulfur positive electrode material for an energy storage battery comprises elemental sulfur and a carbon material matrix; the carbon material matrix comprises graphite, graphene, carbon nanotubes, amorphous carbon, carbon cloth and a mixture of any two thereof.